Developments of Advanced Electrospinning Techniques: A Critical Review - Li, Ya; Zhu, Jiadeng; Cheng, Hui; Li, Guoqing; Cho, Hyunjin; Jiang, Mengjin; Gao, Qiang; Zhang, Xiangwu (WILEY, 2021)
Electrospinning, considered as a low-cost and straightforward approach, attracts tremendous attention because nanofibrous materials with functional properties prepared by it can be widely applied in numerous fields, including rechargeable batteries, filtration, and distillation. This paper aims to provide a comprehensive review of the latest advances in developing this unique technique, which starts with a brief introduction of the advantages of electrospinning and highlights ongoing research activities, followed by its principles and progress. Afterward, the corresponding properties of electrospun nanofibers are discussed. A future vision regarding challenges and perspectives in this area is proposed at the end. It is believed that this review would provide an extensive and comprehensive reference to utilize this advanced technique to generate novel nanofibers performing in high demanding areas.